CRISPR-Based Isothermal Next-Generation Diagnostic Method for Virus Detection in Sugarbeet - Ramachandran, Vanitharani; Weiland, John J.; Bolton, Melvin D. (Frontiers in Microbiology, 2021)
Rhizomania is a disease of sugarbeet caused by beet necrotic yellow vein virus (BNYVV) that significantly affects sugarbeet yield globally. Accurate and sensitive detection methods for BNYVV in plants and field soil is necessary for growers to make informed decisions on variety selection to manage this disease. A recently developed CRISPR-Cas based detection method has proven highly sensitive and accurate in human virus diagnostics. Here, we report the development of a CRISPR-Cas12a based method for detecting BNYVV in the roots of sugarbeet. A critical aspect of this technique is the identification of conditions for isothermal amplification of viral fragments. Towards this end, we have developed a reverse-transcription (RT) recombinase polymerase amplification (RPA) for detecting BNYVV in sugarbeet roots. The RT-RPA product was visualized, and its sequence was confirmed. Subsequently, we designed and validated the cutting efficiency of guide RNA targeting BNYVV via in vitro activity assay in the presence of Cas12a. The sensitivity of CRISPR-Cas12a trans reporter-based detection for BNYVV was determined using a serially diluted synthetic BNYVV target sequence. Further, we have validated the developed CRISPR-Cas12a assay for detecting BNYVV in the root-tissue of sugarbeet bait plants reared in BNYVV-infested field soil. The results revealed that BNYVV detection is highly sensitive and specific to the infected roots relative to healthy control roots as measured quantitatively through the reporter signal. To our knowledge, this is the first report establishing an isothermal RT-RPA and CRISPR-based methods for virus diagnostic approaches for detecting BNYVV from rhizomania diseased sugarbeet roots.